Penerapan kerangka kerja DPSIR terhadap sampah dan dampaknya pada lingkungan di Kawasan Wisata Pantai Pangandaran - Priatna, Yogie Yedia; Tarigan, Billy Jones; Triputra, Mochammad Firmansyah; Kustiwan, Iwan (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2024)
The study aims to analyze waste management issues in the Pangandaran Beach tourist area using the DPSIR (Driver, Pressure, State, Impact, Response) framework. This approach is used to identify the driving factors, pressures, environmental conditions, impacts, and responses related to waste problems in the area. The analysis shows that population growth, increased tourism activities, and the unique geographical and oceanographic characteristics of the region have placed significant pressure on the coastal ecosystem. This has led to a decline in the quality of the beach, water, and marine ecosystems. The resulting impacts include environmental degradation, a diminished quality of tourist experiences, and threats to human health and marine life. The study recommends a comprehensive and integrated approach, involving technological innovation, public education, and collaboration among stakeholders, to address waste issues at Pangandaran Beach. The implementation of these strategies is expected to foster sustainable coastal tourism management.